PERANCANGAN JARINGAN DENGAN PROTOKOL EIGRP DI UNIVERSITAS UDAYANA - Ida Bagus Vidananda Agastya; Dewa Made Wiharta; Nyoman Putra Sastra (Jurnal SPEKTRUM, 2021)
In this journal, a new network is designed in the area of Udayana University, Bukit JimbaranCampus using Cisco Packet Tracer. The purpose of this design is to build a network that can improveefficiency in the process of exchanging data and information. The design uses one dynamic routing,namely Enhanced Interior Gateway Routing Protocol (EIGRP). EIGRP was chosen because thisprotocol is the only protocol that has a backup system. In addition, the network that is designed alsouses a ring topology, with the consideration that the ring topology is the best topology for buildingnetworks with service areas in the form of rotations. Analysis of the designed network performancehas been carried out by sending PING with several scenarios to obtain packet loss, throughput, anddelay parameter values. Based on the research results obtained the same packet loss parametervalue for each case that is 0%, the average value of throughput is 4,398 bps, and the average delayvalue is 10.125 ms. The three results of each of these parameters meet the requirements of theTIPHON in the excellent category and have a class 4 index.